Quantitative Analysis Of Completeness Of Medical Record Document Filling At Public Health Center - Galih Persadha (MBUnivPress, 2022)
Completeness of filling out medical record documents is a must that must be fulfilled to improve the quality of service quality in health care institutions. The community health center is a first-level individual health service facility, by prioritizing promotive and preventive efforts in its working area. Improvement efforts are carried out by conducting regular reviews, both qualitative and quantitative. The quality of the medical record document is reflected in the completeness status if it meets the criteria: completeness of content, accuracy, timeliness and compliance with legal aspects. In the preliminary study, it was found incompleteness in filling out medical record documents. In the Authentication Review found incompleteness that can reduce or even eliminate the value of medical record documents both financially, therapy continuity and law. This study aims to assess the completeness of filling out medical record documents by using quantitative analysis methods on the completeness of filling out medical record documents. The research method used is descriptive with a quantitative approach. The sample in this study was 20 medical record documents from public health centers which were taken randomly using random sampling method from two different public health centers. The results showed that the Patient Identification Review, the Important Reporting Review, the anamneses were 100% complete, the Authentication Review was 87.5% complete and the Correct Documentation Review was 82% complete. The conclusion obtained is that the Authentication Review section of the doctor's name is 79%, the signature of the doctor or nurse is 96% and in the Correct Documentation Review in the section there are scribbles of 12.5%, the use of type-x is 4% and there is an empty section of 37.5 %. Efforts made to improve the quality of the completeness of medical record documents can be carried out by evaluating the implementation of the established SOP and reviewing the provision of rewards and punishments